Developing a Verification and Training Phantom for Gynecological Brachytherapy System - Mahbobeh Nazarnejad; Seied Rabi Mahdavi; Khadijeh Asnaashari; Mahdi Sadeghi; Alireza Nikoofar (Iranian Journal of Medical Physics, 2012)
Introduction Dosimetric accuracy is a major issue in the quality assurance (QA) program for treatment planning systems (TPS). An important contribution to this process has been a proper dosimetry method to guarantee the accuracy of delivered dose to the tumor. In brachytherapy (BT) of gynecological (Gyn) cancer it is usual to insert a combination of tandem and ovoid applicators with a complicated geometry which makes their dosimetry verification difficult and important. Therefore, evaluation and verification of dose distribution is necessary for accurate dose delivery to the patients. Materials and Methods The solid phantom was made from Perspex slabs as a tool for intracavitary brachytherapy dosimetric QA. Film dosimetry (EDR2) was done for a combination of ovoid and tandem applicators introduced by Flexitron brachytherapy system. Treatment planning was also done with Flexiplan 3D-TPS to irradiate films sandwiched between phantom slabs. Isodose curves obtained from treatment planning system and the films were compared with each other in 2D and 3D manners. Results The brachytherapy solid phantom was constructed with slabs. It was possible to insert tandems and ovoids loaded with radioactive source of Ir-192 subsequently. Relative error was 3-8.6% and average relative error was 5.08% in comparison with the films and TPS isodose curves. Conclusion Our results showed that the difference between TPS and the measurements is well within the acceptable boundaries and below the action level according to AAPM TG.45. Our findings showed that this phantom after minor corrections can be used as a method of choice for inter-comparison analysis of TPS and to fill the existing gap for accurate QA program in intracavitary brachytherapy. The constructed phantom also showed that it can be a valuable tool for verification of accurate dose delivery to the patients as well as training for brachytherapy residents and physics students.